Heparin: An old drug for new clinical applications. (1st November 2022) - Wang, Peipei; Chi, Lianli; Zhang, Zhenqing; Zhao, Hongmei; Zhang, Fuming; Linhardt, Robert J.
Abstract: Heparin, an old but first-line anticoagulant, has been used over a century. It is a heterogeneous, linear, highly sulfated, anionic glycosaminoglycan with a broad distribution in relative molecular weight and charge density. These structural properties allow heparin to selectively interact with multiple proteins, leading to heparin's various pharmacological functions, such as anticoagulant, anti-viral, anti-tumor and anti-inflammatory activities. Clinical data suggest that unfractionated heparin or low molecule weight heparin could decrease mortality in COVID-19 patients with sepsis-induced hypercoagulation through the anticoagulant, anti-viral and anti-inflammatory activities of these drugs. Thus, the non-anticoagulant activity of heparin has again aroused attention. This review highlights recent advances in the preparation of heparin-derived drugs and clinical research on its non-anticoagulant properties over the past decade, to further the development and utilization of these important drugs. Graphical abstract: Unlabelled Image